The why and how of working time reduction [Korean version] - De Spiegelaere, Stan; Piasna, Agnieszka (Seoul, 2017)
"This guide maps the discussion on working time reduction by examining the recent trends, the different reasons for implementing such a reduction, and the ways in which it can be organised. Illustrated with numerous real-life examples and insights from research, this guide is a valuable resource for anybody wishing to know more about the working time reduction debate. The guide shows that there is no ‘one best way’ of reducing working time. The design of the experiment should be adapted according to the purpose of the reduction. At the same time, it is clear that there is a great need for large-scale experimentation with organised working time reduction, as the current reduction through the proliferation of part-time work does not guarantee an equal redistribution of work nor does it promote gender equality."